Criteria for Choosing ways to Plan and Solve Problems and Errors that Elementary Sсhool Students Have Made in Writing Works - Nazarova Nilufar Raxmatboy qizi (International Journal on Integrated Education, 2021)
This article examines written work to improve the speech of primary school students, including teaching methods for writing essays, and provides various recommendations and conclusions.Based on the topic, interactive lessons, lesson plans, and special training programs can be created to create an interactive learning environment for primary school students to develop their writing skills.The effectiveness of the use of written work in the educational process in the development of speech in primary school students will be improved.